A Wireless Sensor Network for Agricultural Applications Using ARM7 (International Journal of Engineering and Computer Science, 2017)
— The agricultural field monitoring has become very important in these recent times. The farmers are struggling in many ways to get the yield from the fields. The farmers thus must have to struggle a lot in order to maintain their fields such that their crops are not damaged and they must get the required crops. Few technologies are being developed which are used to monitor the status of the fields. This project is also developed in order to provide the monitoring of the field’s condition. In this project, we are continuously checking water in the field using sensor. If there is no water in the field, the sprinkler should be ON for that indication we have used one motor for pumping and if the water is more in the field automatically motor should be OFF and in rainy season whenever water is more field ending (spool) will be damaged so to avoid that we have used another sensor at field ending (spool) if the water level is high the gate should be open otherwise gate should be closed using a motor and another motor is used to sprinkle the fertilizers. In the field, if fire is occurred user have to receive a message that fire accident had occurred then sprinklers automatically ON in order to control the fire.  Thus, this method will be more advantageous for the monitoring of the fields.